Relevance of sex education for young people with intellectual disability: A systematic review - Mathew, Manoj P.; George, Anna; Mishra, Nishtha; Jose, Ajith; Sharma, Jyoti; Kumar, A. P. Senthil (International journal of health sciences, 2022)
Of the various socially relevant crises of the world one that ought to be brought to limelight is the encumbrances faced by people who are intellectually disabled.People with intellectual disability are ones who face extreme challenges in their personal as well as social life. This paper accounts for a systematic review of issues and challenges in sexual life of people with intellectual disability. For this ssample datahas beencollected from the online database like Scopus, Pub Med, and Google scholar and classified into distinct sections based on a bumper of factors - sexual aspects, sexual abuse/violence and role of care givers to people with intellectual disability. The chief culprit behind the sexual problems in people with intellectual disability is the lack or absence of precise sexual education.So, proper and sound sexual education must be ensured to the people with intellectual disability to root out the all the sexual health complications.